隔爆型多级带传输多触摸屏多CAN板并联远距集控装置 (2018)
本发明专利为隔爆型多级带式输送多触摸屏多CAN板远距离集控装置，包括洗煤厂多级带式运输监控装置，多个触摸屏和CAN板并联后，通过RS485串口线与PLC串口连接；抱闸检测开关、主接触器的触点反馈检测开关与PLC的输入输出端点连接；各个从机出现通信故障，及时发现。具有抱闸、烟雾、堆煤、打滑、电机温度、前滚筒温度、后滚筒温度、前跑偏、中跑偏、后跑偏的保护功能，并可在触你摸屏中进行解除/投入设置；各个触摸屏中显示电流、电压和功率，能够实现具有多触摸屏多CAN板远距监控的功能，适用于多数据的处理，数据传输快，信号衰减小，抗干扰能力强。其功能齐全、性能可靠。 An explosion-proof multistage belt transportation multi-touch-screen multi-CAN-board parallel long-distance centralized control device comprises an explosion-proof multistage belt transportation monitoring device. Multiple touch screens (HMI1, HMI2, HMI3, HMI4) are connected in parallel with CAN boards (CAN1, CAN2, CAN3, CAN4) and then are connected to a PLC serial port (Port0) by means of RS485 serial port lines; a band-type brake detection switch and a contact feedback detection switch of a main contactor are connected to input endpoints of a PLC; and in a case in which secondary machines encounter communication faults, the faults can be found in time. The device has protection functions for a band-type brake, smoke, coal stacking, sk